2014
DOI: 10.3892/ijmm.2014.1644
|View full text |Cite
|
Sign up to set email alerts
|

Administration of erythropoietin exerts protective effects against glucocorticoid-induced osteonecrosis of the femoral head in rats

Abstract: Accumulating evidence has indicated that erythropoietin (EPO) plays a role in anti-apoptosis and tissue protection in a number of human diseases. The present study was implemented to evaluate these anti-apoptotic and tissue-protective effects in glucocorticoid-induced osteonecrosis in rats. Osteonecrosis was induced by low-dose lipopolysaccharide and subsequent high-dose methylprednisolone pulse. Rats in the preventive group were treated with 500 U/kg/day recombinant human EPO (rhuEPO) for 1 week. Hematologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…These two free radicals have very strong oxidizing activity and cytotoxicity, resulting in bone damage. NO has a dual function in bone absorption and inhibits the growth of osteoblasts or even has toxic effects during bone formation (1). However, the effect of NO on the process of SANFH development is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two free radicals have very strong oxidizing activity and cytotoxicity, resulting in bone damage. NO has a dual function in bone absorption and inhibits the growth of osteoblasts or even has toxic effects during bone formation (1). However, the effect of NO on the process of SANFH development is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies have found that the primary cause of femoral head necrosis is steroid hormones, which is the main reason for the disease (1). The occurrence of femoral head necrosis is associated with the administration method and dose of the hormones, and is affected by individual differences and sensitivities (2).…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent data using an animal model also supports the use of exogenous erythropoietin in the treatment of corticosteroid induced ONFH. 23 Operative treatment of ONFH consists of core decompression, nonvascularized bone grafting, vascularized bone grafting, and administration of bone morphogenetic proteins, stem cell therapy, proximal femoral osteotomies, and hip arthroplasty. 7 The patient in this case report had advanced ONFH on the left (Ficat and Arlet stage III) and was treated with a total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…We divided all rats into four groups: control group (7 rats), methylprednisolone treatment group (MPS, 8 rats), CAPE treatment group (8 rats) and MPS+CAPE administered group (8 rats). The rats of group MPS and CAPE+MPS, On days 2, 3 and 4 were treated with 20 mg/kg/day methylprednisolone (MPS; Pfizer Pharmaceutical, Puurs, Belgium) intramuscularly 22) . 10 μmol/kg/day CAPE was intraperitoneally injected to the rats of group CAPE from 13 weeks of age for 4 weeks 23) .…”
Section: Methodsmentioning
confidence: 99%